Application of Human Factors in the Development Process of Immersive Visual Technologies: Challenges and Future Improvements - Saghafian, Mina; Sitompul, Taufik Akbar; Laumann, Karin; Sundnes, Kristina; Lindell, Rikard (Frontiers in Psychology, 2021)
This study investigates how Human Factors (HF) is applied when designing and developing Immersive Visual Technologies (IVT), including Augmented Reality, Mixed Reality, and Virtual Reality. We interviewed fourteen people working at different organizations, that develop IVT applications in the Nordic region. We used thematic analysis to derive themes from the interviews. The results showed an insufficient knowledge and application of HF in IVT development, due to the lack of awareness of both scope and significance of HF, resource allocation strategy, market inertia, stakeholder’s involvement, standardization of HF application and IVT uses, and technology maturity. This situation could be improved by allocating expert at each HF level, adjusting organizational strategy to balance resource allocation, educating and training developers and user organizations to raise awareness and encourage co-creative design to enhance knowledge sharing, create a sense of ownership amongst stakeholders, and ensure the usefulness of the technology to the user’s work.